Development and preliminarily validation of the Complementary Medicine Disclosure Index. Issue 6 (June 2020) - McIntyre, Erica; Foley, Hope; Diezel, Helene; Harnett, Joanna; Adams, Jon; Sibritt, David; Steel, Amie
Highlights: Developed a tool measuring reasons for complementary medicine disclosure behavior. The Complementary Medicine Disclosure Index had acceptable construct validity. Index consists of two second-order measurement models: non-disclosure and disclosure. Concerns about the medical encounter the most important reason for non-disclosure. Abstract: Objective: Non-disclosure of complementary medicine (CM) use to doctors is associated with health risks. No standardised, validated instrument exists to measure reasons for CM use disclosure behaviour to doctors in clinical research or practice. This study aims to develop and validate an index that measures the relative importance of reasons for CM disclosure and non-disclosure. Methods: Using data from the Complementary Alternative Medicine Use Health Literacy Disclosure Study (N = 2019), we developed a CM Disclosure Index (CMDI) using a formative measurement approach. The adequacy of the measurement models was assessed by conducting variance-based structural equation modelling using partial least squares to analyse multicollinearity, significance and relevance of the formative indicators to their relative primary constructs. Results: The CMDI consists of two second-order measurement models, each with three sub-domains, and demonstrated acceptable construct validity indicating the index is a useful measure to identify the reasons for CM use disclosure behaviour. Conclusion: The CMDI provides a preliminary tool to measure the relative importance of the reasons for CM use disclosure and non-disclosure to doctors. Practice implications: Understanding patients' reasons for disclosure and non-disclosure can assist in developing targeted interventions to both patients and practitioners to facilitate effective patient-practitioner communication and improve patient safety.